2009
DOI: 10.1007/s10545-009-1178-9
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy case of Gaucher disease type I in a patient on enzyme replacement therapy. Comments on the dynamics of persistent storage process

Abstract: We report a female patient with Gaucher disease (GD) type I on ERT (imiglucerase) for 5 years, which led to a significant general improvement. Aged 59 years she underwent an episode of altitude sickness followed by sepsis, disseminated intravascular coagulation, and multiorgan failure. She succumbed to a cerebral haemorrhage. Autopsy revealed liver cholestatic cirrhosis and multifocal liver carcinoma with immunophenotype compatible with cholangiocarcinoma. Analysis of the storage process revealed its absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The authors found foamy or vacuolated GCs in the bone marrow which were located closely to the adipose tissue. Ultrastructural examinations of these foamy GCs revealed lipid droplets in the cytosol, separated from the lysosomal compartments [11]. Two years later, in 2011 our group reported for the first time foamy GCs in the living individual [28].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The authors found foamy or vacuolated GCs in the bone marrow which were located closely to the adipose tissue. Ultrastructural examinations of these foamy GCs revealed lipid droplets in the cytosol, separated from the lysosomal compartments [11]. Two years later, in 2011 our group reported for the first time foamy GCs in the living individual [28].…”
Section: Discussionmentioning
confidence: 87%
“…infection, ischaemia). In 2009, Hůlková et al published an autopsy case of a 59 year old woman diagnosed with GD1 which was treated with ERT [11]. The authors found foamy or vacuolated GCs in the bone marrow which were located closely to the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard methods were employed to examine the lysosomal system, and the activities of dehydrogenases of α-glycerophosphate, succinate, nicotineamide adenine dinucleotide (NADH) and cytochrome C oxidase (COX) as described in our in previous publications. 5,6) Histological examinations showed hypertrophy and partial disarray of cardiomyocytes with disperse interstitial fibrosis ( Figure 4). Cardiomyocytes exhibited focal accumulation of glycogen.…”
Section: Case Reportmentioning
confidence: 99%
“…Although the severity and frequency of bone pain and bone crisis may be reduced rapidly (Pastores et al 1993;Beutler et al 1995;Charrow et al 2007), improvement of bone marrow (BM) involvement can take up to 3 years (Poll et al 2001) and may respond better to higher doses of ERT (de Fost et al 2006). A recent autopsy case report of a GD1 patient on long-term ERT comments on the persistent storage of Gaucher cells in the BM as quantified via fatfraction measurement (Hůlková et al 2009). Gaucher cells were primarily noted in adipose marrow rather than in hematopoietic marrow and were observed to have phagocytosed some of the lipid contents of the surrounding adipocyte tissue.…”
Section: Introductionmentioning
confidence: 99%